2016
DOI: 10.1055/s-0042-115414
|View full text |Cite
|
Sign up to set email alerts
|

Was kosten uns Dolmetscher? – Eine retrospektive Analyse der Dolmetscherkosten in der Behandlung von Flüchtlingen in einer Psychiatrischen Institutsambulanz in Berlin

Abstract: Clinical diagnostics of mental disorders especially among refugees and asylum seekers come with unique difficulties: language barriers, different forms of expression and concepts of the understanding of mental illness as well as a different cultural background. Therefore professional interpreters are needed but associated with a higher effort related to costs and time. We conducted a retrospective analysis of costs, which incurred by the use of professional interpreters in our outpatient clinic in Berlin, Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…A study on Turkish migrants showed that rehabilitation treatment was less effective due to intercultural communication barriers [14]. Given these shortcomings, a study on psychiatric care for refugees in Berlin showed that using professional interpreters' services prevents wrong diagnoses and unnecessary diagnostics, thus ensuring adequate treatment [15]. This relationship between professional interpretation and higher quality of care and patient safety could was also shown in a systematic review [16].…”
Section: Discussionmentioning
confidence: 98%
“…A study on Turkish migrants showed that rehabilitation treatment was less effective due to intercultural communication barriers [14]. Given these shortcomings, a study on psychiatric care for refugees in Berlin showed that using professional interpreters' services prevents wrong diagnoses and unnecessary diagnostics, thus ensuring adequate treatment [15]. This relationship between professional interpretation and higher quality of care and patient safety could was also shown in a systematic review [16].…”
Section: Discussionmentioning
confidence: 98%
“…Linkage to psycho therapists had also been seen as necessary and as has finding a solution for financing language interpreters [35]. Compared to the average waiting period of 23.1 weeks [36] (= 5.7 months) for German citizens, the waiting periods with 12 to 24 months for refugees in Cologne were at least twice as long.…”
Section: Discussionmentioning
confidence: 99%
“…Según evidencia internacional, los facilitadores deberían tener, como mínimo, entrenamiento en mediación intercultural (7,8) , pues la interpretación de indicaciones médicas es un trabajo delicado, donde los profesionales de salud pueden exponerse a mayor riesgo médico legal (27) . La disminución del gasto público es internacionalmente reconocida como ventaja de contar con FI, pues las asignaciones de intérpretes permiten un tratamiento más efectivo y específico, evitando cronicidad, mejora la adherencia y promueve la satisfacción usuaria (10,28,29) .…”
Section: Discussionunclassified
“…En otros casos, existe incorporación formal de personas que llevan a cabo esta labor en el sistema de salud (7)(8)(9) . Sobre su efectividad, un estudio en Alemania indica que, aunque en un principio el costo es más alto por la asistencia de intérpretes lingüísticos, a largo plazo estos costos disminuyen, pues permite un tratamiento orientado a los objetivos terapéuticos, evitando la cronicidad y diagnósticos erróneos (10) . Otros estudios mencionan que el intérprete transmite aspectos culturalmente específicos, como la comprensión de enfermedad, lo que aumenta la efectividad de los equipos de salud para responder las necesidades particulares del usuario (11,12) .…”
Section: Mensajes Clave Introducciónunclassified